2021
DOI: 10.1088/1755-1315/807/2/022113
|View full text |Cite
|
Sign up to set email alerts
|

Host range of Exallomochlus hispidus (Morrison) (Hemiptera: Pseudococcidae) in West Java, Indonesia

Abstract: Exallomochlus hispidus (Morrison) (Hemiptera: Pseudococcidae) is a polyphagous mealybug with a wide host range. Many of them are fruits that have high economic value and potential export commodities. In addition, E. hispidus is a quarantine pest so that its presence can be an export barrier. The purposive sampling method were used to take plant samples. Host plants were sampled in 4 districts in Bogor, Sukabumi, Purwakarta, and Garut, West Java. Mealybugs and their host plants were put in a paper bag and taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The mealybug Exallomochlus hispidus is polyphagous with a variety of hosts ranging from fruit trees, medicinal plants, and weeds [1]. Williams reported that there are 41 host plants from 30 families in the Asian region [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mealybug Exallomochlus hispidus is polyphagous with a variety of hosts ranging from fruit trees, medicinal plants, and weeds [1]. Williams reported that there are 41 host plants from 30 families in the Asian region [2].…”
Section: Introductionmentioning
confidence: 99%
“…Williams reported that there are 41 host plants from 30 families in the Asian region [2]. The major host plants were fruit crops including cocoa, duku, rambutan, sapodilla, soursop, mangosteen and lemon [1]. One of the fruits that host and has export value is the mangosteen.…”
Section: Introductionmentioning
confidence: 99%